2020
DOI: 10.3390/catal10121407
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Materials for the Development of Highly Dispersed Metal Catalysts: Towards Highly Performant Catalysts for Fine Chemical Synthesis

Abstract: Single-atom catalysts (SACs), consisting of metals atomically dispersed on a support, are considered as advanced materials bridging homogeneous and heterogeneous catalysis, representing the catalysis at the limit. The enhanced performance of these catalysts is due to the combination of distinct factors such as well-defined active sites, comprising metal single atoms in different coordination environments also varying its valence state and strongly interacting with the support, in this case porous carbons, maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…Despite some limitations, many materials, including carbon-based materials [21][22][23][24][25][26][27], hybrid polymers [13], metal oxides [17,[28][29][30][31][32][33][34][35], metal-organic frameworks [36,37], and zeolites [38][39][40][41] have been prepared via printing so far.…”
Section: Highlightsmentioning
confidence: 99%
“…Despite some limitations, many materials, including carbon-based materials [21][22][23][24][25][26][27], hybrid polymers [13], metal oxides [17,[28][29][30][31][32][33][34][35], metal-organic frameworks [36,37], and zeolites [38][39][40][41] have been prepared via printing so far.…”
Section: Highlightsmentioning
confidence: 99%
“…The high temperature pyrolysis method has been a prominent way to synthesise nanosized carbon-supported SACs. This method appears to include the construction of a template-sacrificial approach by acid leaching or calcination at temperatures ranging from 400 to 600 • C [137][138][139][140]. Li and colleagues proved this strategy in the synthesis of Zn-N-C SACs and Fe-N-C SACs using ZnCl 2 and FeCl 3 .6H 2 O as a precursor for the ORR process, and the findings of XANES and EXAFS tests demonstrated that Zn-N 4 and Fe-N 4 were the main active sites in the Zn-N-C SACs and Fe-N-C SACs [141].…”
Section: Top-down Synthesis Strategies Of Sacs and Saasmentioning
confidence: 99%
“…[12][13][14][15] The main goal of applying catalyst support is to improve the stability of catalysts and also to provide a sufficient number of catalytic active sites on the surface of supports. A variety of solid materials including polymer-based materials, [16][17] porous materials, [18][19] magnetic nanoparticles [20][21] and carbon-based materials [22] were selected as solid supports to design of an effective heterogenized catalyst. Because of high density, excellent stability, great strength, high specific surface area and also cost effectiveness, the use of carbon-based catalyst supports such as graphene oxide, carbon nanotubes, carbon nanofibers, carbon nitride, and activated carbon is widely extended in the case of experimental techniques.…”
Section: Introductionmentioning
confidence: 99%